Liver fibrosis-4 score predicts outcome of patients with ischemic stroke undergoing intravenous thrombolysis - Norata, Davide; Lattanzi, Simona; Broggi, Serena; Rocchi, Chiara; Bartolini, Marco; Silvestrini, Mauro (Frontiers in Neurology, 2023)
Some evidence suggests a possible influence of liver disease on stroke prognosis. We investigated the association between fibrosis-4 (FIB-4) score, a marker of liver disease, and the 3-month outcome in patients with ischemic stroke undergoing intravenous thrombolysis. We also evaluated the rate of symptomatic intracranial hemorrhage after thrombolysis. In this prospective cohort study, we enrolled consecutive patients with ischemic stroke treated with thrombolysis who had a 3-month follow-up. The FIB-4 score was calculated and the validated cut-off values were used to indicate high/low risk of advanced liver fibrosis. The primary outcome was 3-month poor prognosis estimated as a modified Rankin scale score ≥3. Of the 264 included patients, 131 (49.62%) had a 3-month mRS ≥3, with a significantly higher FIB-4 score, compared to those with a mRS <3 score (adjp <0.001). When adjusted for possible confounders by multivariate logistic regression, FIB-4 score remained a significant predictor of poor outcome (OR 1.894, p = 0.011), along with history of atrial fibrillation (OR 3.488, p = 0.017), admission NIHSS score (OR 1.305, p < 0.001), and low values of hemoglobin (OR 0.730, p < 0.001). Mechanical thrombectomy had a favorable effect on patients' outcome (OR 0.201, p = 0.005). The risk of poor 3-month outcome was significantly higher among the 32 patients (12.1%) with high risk of severe fibrosis (p = 0.007). FIB-4 score values were also related to symptomatic intracranial hemorrhage (p = 0.004), specifically among patients with high probability of advanced hepatic fibrosis (p = 0.037). FIB-4 score can be considered as a promising independent predictor of poor prognosis in patients with acute ischemic stroke undergoing intravenous thrombolysis.